Deteksi dan Identifikasi Nematoda Aphelenchoides besseyi dari Benih Padi - Rizky Mailani Rahman; Abdul Munif; Fitrianingrum Kurniawati (Jurnal Fitopatologi Indonesia, 2018)
Detection and Identification of Aphelenchoides besseyi from Rice SeedsAphelenchoides besseyi is an important plant parasitic nematode on rice and causes yield loss up to 54%. The nematodes are able to survive for 8 months to 3 years after harvest and can be transmitted through seeds. The research was conducted to determine infestation of A. besseyi on seeds of five rice cultivars, namely Pak Tiwi 1, IR64, Ciherang, IPB 3S, and SL 8 SHS; and to identify A. besseyi by morphological and molecular techniques using polymerase chain reaction (PCR), and nucleotide sequensing. The nematodes were extracted from 5 g seeds of each cultivar by modified Baermann funnel method. Morphological identification was done by observing semipermanent slide of adult nematodes. Molecular identification by PCR used universal primers to amplify ITS rDNA followed by nucleotide sequencing. The result showed that A. besseyi were found on 5 rice cultivars in varies numbers. A. besseyi has specific morphological character, i.e. it has 2–4 mucro (tail tip) arranged in a star shaped that can be distinguished from other species. DNA fragments with approximately 830 bp in length was successfully amplified.  Further nucleotide sequence analysis showed that A. besseyi Indonesia (isolate Pak Tiwi 1) had the higest homology level of 98.1% with A. besseyi isolat India Drr Ab 1 and Kolkata, 98.0% with India Hyderabad, 97.8% with China HB, 97.7% with Taiwan HW, and 97.5% with Cina AB11.